UMKM Go Digital: Memanfaatkan Fintech dan Sumber Pendanaan untuk Ekspansi Bisnis - Lubis, Firsty Ramadhona Amalia; Az zakiyyah, Nurul Azizah; Sukarniati, Lestari; Basia, Lusmino; Cholida, Maya Nur; Apriliana, Dwi; Gatari, Altis Puspa; A'yun, Indanazulfa Qurrota; Nasir, Muhammad Safar (Indonesian Scientific Journal, 2025)
Pelatihan bertema